The ILO Standards and Canadian Labour Legislation - Zeytinoglu, Isik (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
The author analyzes the impact of the International Labour Organization 's Freedom of Association Standards on Canadian labour legislation in the last decade.